AN INQUIRY INTO THE PROCESSES OF LEXICAL EXPANSION IN CURRENT ENGLISH - Kriaučiūnienė, Roma; Sangailaitė, Vilija (Verbum, 2016)
The current paper focuses on the study of novel lexical items, i. e. the processes involved in the making of new words, in order to discover which methods contribute to the expansion of the current English lexicon. The research is based on the new words coined since 2004 which are included in the Oxford English Dictionary (OED) Online (ensuring that the items in the sample cover various semantic fields, are of diverse origins, and all are already accepted into the working vocabulary). Two objectives are completed to explore the subject and achieve its aim: 1) to establish the concept of new words and to overview the processes of lexical expansion in the English language, and 2) to determine which methods are employed and which are absent in the creation of new words in current English by analyzing the novel lexical items retrieved from the OED Online. Quantitative and qualitative methods are applied in this study. The results indicate that the concept of new words is not straightforward in the English language. More often than not, the terms neologisms and new words are used synonymously to refer to recent, novel lexical items recognized and used by the language community. English has an extensive inventory of word-forming tools classified into these distinct categories: word-formation, semantic change, borrowing, and other; each further subdivided into various processes. Overall, the subtypes of word-formation – derivation, shortening and compounding – are used the most in the creation of recent additions to the lexicon. Predominantly, the findings are consistent with the tendencies of lexical expansion observed in previous studies.
Keywords: lexical expansion; word formation; neologisms; new words